Efektivitas Program Pendidikan Bina Lingkungan pada Masyarakat Nelayan Kelurahan Kota Karang Raya Kota Bandar Lampung - Pratama, Alfi Wira (JURNAL SOSIOLOGI, 2015)
This research aims to understand and analyze the effectiveness of Bina Lingkungan program in Kota Karang Raya fisherman community. The approach in the research is quantitative approach, this approach to the primary use strategy for research using a questionnaire survey data collection. Respondents in this research are 67 people, the sample in this experiment using purposive sampling techniques. An analysis of the data used in this research using percentage technique and factor analysis. Research shows: (1) Many fishermen in Kota Karang Raya village have children more than three. The number of dependents while a minimum income as fishers make their family needs not enough, especially the need for education of the children. (2) On the variables of Bina Lingkungan for knowledge program, the purpose of Bina Lingkungan, benefits of Bina Lingkungan and accuracy of targets of Bina Lingkungan, the results is very effective. While on the variables of socialization and monitoring of Bina Lingkungan the results really ineffective. Overall, research on the effectiveness of the Bina Lingkungan program in Kota Karang Raya fishermen community can be concluded quite effective, because the calculation on the effectiveness of the results 77,31 %. In accordance with Litbang Depdagri the value of this percentage included in the category of quite effective. (3) based on the results of factor analysis, beneficial of program Bina Lingkungan factor have value the influence of most large eigenvalue with a total of 2,398 and value of varianced 29,969 % explained as much as.Keywords: Effectiveness program, bina lingkungan, fisherman community